2021
DOI: 10.1177/0003134821989043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anticoagulation and Antiplatelet Use in Trauma Patients on Mortality and Length of Stay

Abstract: Background Though many trauma patients are on anticoagulation or antiplatelet therapy (AAT), there are few generalizable data on the risks for these patients. The purpose of this study was to analyze the impact of anticoagulation (AC) and antiplatelet (AP) therapy on mortality and length of stay (LOS) in general trauma patients. Methods A retrospective review was performed of patients in the institutional trauma registry during 2019 to determine AAT use on admission and discharge. Outcomes were compared using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…In contrast to Narula's study [ 1 ] which demonstrated higher rates of mortality in patients taking warfarin and DOACs, we found that use of preinjury clopidogrel increased mortality and platelet use in the first 24 h while warfarin and DOAC use trended toward higher mortality ( Table 2 ). Warfarin was significantly associated with higher risk of serious in-hospital complications, as well as increased hospital and ICU length of stay.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to Narula's study [ 1 ] which demonstrated higher rates of mortality in patients taking warfarin and DOACs, we found that use of preinjury clopidogrel increased mortality and platelet use in the first 24 h while warfarin and DOAC use trended toward higher mortality ( Table 2 ). Warfarin was significantly associated with higher risk of serious in-hospital complications, as well as increased hospital and ICU length of stay.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies, including those by Narula and Reina et al [ 1 , 2 ] have investigated outcomes in trauma patients taking clopidogrel, warfarin, or DOACs prior to injury. However, there remains a paucity of literature on patient outcomes in those taking AP/AC who sustain thoracoabdominal trauma requiring surgical intervention in the first 24 h, allowing this to be the first study of its kind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the discharge outcomes of trauma patients involve various factors, including the length of hospitalization, rates of mortality, rates of readmission, and the distinction between discharge to home and discharge to healthcare facilities [5][6][7][8].…”
mentioning
confidence: 99%